Quality of life of patients with kidney failure in sub-Saharan Africa: protocol for a systematic review of quantitative studies - Snead, Charlotte M; Seneschall, Charlotte C; Davids, M Razeen; Young, Taryn; Caskey, Fergus J; Effa, Emmanuel E (African Journal of Nephrology, 2023)
Introduction: The burden of chronic kidney disease (CKD) is rising in sub-Saharan Africa. Access to kidney replacement therapy (KRT) remains limited and modelling suggests a significant hidden burden of kidney failure managed without KRT. Kidney failure is contributing to serious health-related suffering (SHS) at a global level. Despite this, access to palliative care remains extremely disparate. There is an urgent need for greater palliative care provision for patients with kidney failure in sub-Saharan Africa. To inform this, it is important to understand their current quality of life. This article outlines our review protocol, ensuring transparency of our planned methods and reporting. Methods and analysis: A comprehensive search will be conducted of MEDLINE (Ovid), EMBASE, CINAHL, African Index Medicus and Africa Journals Online. ProQuest Dissertations & Theses Global will be searched for grey literature. Eligible sources will be quantitative observational studies, conducted in sub-Saharan Africa, and published in English or French. The primary outcome measure will be quality of life of those with kidney failure, measured using a validated quality of life tool. Abstract screening, data extraction and risk of bias assessments will be conducted independently by two reviewers. Meta-analysis will be performed on study subgroups, if appropriate, based on heterogeneity of included studies; otherwise results will be summarised narratively. This protocol is structured according to the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) guidance. Ethics and dissemination: Ethical approval is not required because this review will synthesise published data. Findings will be disseminated in a peer-reviewed journal. PROSPERO registration ID: 275434